Renoprotective effect of trolox against ischaemia-reperfusion injury in rats - Orawan Wongmekiat (2018)
1. Although α-tocopherol has been shown to improve renal function following ischaemia-reperfusion (I/R) injury, its clinical use is not common because α-tocopherol requires several days of pretreatment to exhibit anti-oxidative benefits. The advent of trolox, a water-soluble analogue of α-tocopherol, has raised the possibility that this compound may function more rapidly during acute oxidative stress than the conventional α-tocopherol. 2. The present study was undertaken to determine the effects of the short-term administration of trolox on renal excretory function following I/R in rats. 3. Male Wistar rats were subjected to 45 min unilateral renal artery occlusion followed by 120 min reperfusion. The control I/R group was subjected to I/R and received saline as an intravenous bolus (2 mL/kg) followed by a continuous infusion of 2 mL/kg per h starting 30 min before ischaemia, whereas the three trolox-treated I/R groups were given an i.v. bolus of trolox (2.5 mg/kg) followed by a continuous infusion (12 mg/kg per h) starting at 30 min before ischaemia, 5 min before reperfusion and 5 min after reperfusion, respectively. Renal function, malondialdehyde, glutathione and histopathology were evaluated. 4. Ischaemia-reperfusion produced a significant deterioration of renal function, which was accompanied by an elevated malondialdehyde and depleted glutathione content. Kidneys from control I/R rats demonstrated tubular cell transformation, brush border loss, vacuolation, cast formation and tubular obstruction. These changes were attenuated by trolox treatment, with the best improvement achieved when trolox was delivered 5 min before reperfusion. 5. The results demonstrate the renoprotective effects of the short-term administration of trolox on I/R injury. These findings indicate the ability of trolox to overcome a major drawback of using α-tocopherol and suggest that trolox may offer a therapeutic advantage over α-tocopherol in acute ischaemic renal failure settings. © 2007 The Authors.